Assessment of Water Quality in Sarawak River - Vanessa Rae, Dunstan (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Water quality of Sarawak River is deteriorating due to the impact from increasing anthropogenic activities and population. The present study has been conducted to assess the status of physico-chemical parameters and the concentrations of selected heavy metals to understand the current condition of water quality at Sarawak River, Malaysia. Water quality was determined at 16 stations along Sarawak River. In-situ parameters including depth, temperature, pH, turbidity, salinity and DO were ranged between 2.4-15.3 m, 27.45-29.76 °C, 6.66-7.90, 19.67-51.33 NTU, 0.02-21.71 ppt, 2.74-4.87 mg/L, respectively. Ex-situ parameters such as BOD5, COD, TSS, TAN, NO3-N and TP were ranged between 0.65-2.44 mg/L, 1.00-136.67 mg/L, 93.33-123.33 mg/L, 0.14-1.63 mg/L, 0.06-0.32 mg/L and 0.15- 0.23 mg/L, respectively. The heavy metal concentrations in the water sample is in the order: Fe> Co> Cu> Mn> Pb> Al> Cd. One-Way ANOVA revealed that there are significant differences (p < 0.05) between the stations. Pearson correlation showed significant correlation between heavy metals and physicochemical parameters in water. Most of the station were considered slightly polluted and classified as Class III and require extensive treatment for domestic purposes. The present study is highly significant in providing useful baseline information for better and sustainable management of Sarawak River’s water quality.